Services for older adults in rural primary care memory clinic communities and surrounding areas: a qualitative descriptive study - Valerie Elliot; Julie Kosteniuk; Megan E. O'Connell; Chelsie Cameron; Debra Morgan (BMC, 2024)
Abstract Background/Objectives As part of a larger study, and in collaboration with rural primary health care teams, RaDAR (Rural Dementia Action Research) primary care memory clinics have evolved and continue to spread in communities across southeast Saskatchewan, Canada. This study focuses on the geographical areas of the four communities where RaDAR memory clinics were first developed and implemented and describes the services and supports available to older adults including memory clinic patients and families living in these areas. Our goal was to identify and describe existing programs and gaps, create inventories and maps, and explore the service experiences of family caregivers of people living with dementia in these rural areas. Methods Using a qualitative descriptive design, an environmental scan of services was conducted from December 2020 to April 2021 using focus groups (n = 4) with health care providers/managers (n = 12), a secondary source (e.g., program brochures) review, and a systematic internet search targeting four RaDAR memory clinic communities and surrounding areas via community websites, online resources, and the 211 Saskatchewan service database. Data were analyzed using content analysis; findings informed semi-structured interviews with caregivers (n = 5) conducted from March to July 2022, which were analyzed thematically. Geographic areas explored in this study covered an area of approximately 5666 km2. Results From the scan, 43 services were identified, categorized into 7 service types, and mapped by location. Seventeen services were dementia-related. Services included social/leisure activities (n = 14), general support/referrals (n = 13), transportation (n = 7), information/education (n = 4), respite (n = 2), in-home care (n = 2), and safety (n = 1). Service levels included local (n = 24), provincial (n = 17), and national (n = 2), and were offered in-person, remotely (or both) with 20 services across 4 service types offered remotely. In general, most services had no fees, involved self-referral, and providers had a range of education/training. Key interview themes reflected the need for locally available, accessible services that offer (i) individualized, flexible, needs-based approaches, (ii) in-home care and continuity of care, and (iii) both formal and informal supports. Key gaps were identified, including (i) locally accessible, available services and resources in general, (ii) dementia-related training and education for service providers, and (iii) awareness of available services. Benefits of services, consequences of gaps, and recommendations to address gaps were reported. In general, service providers and program participants were an even mix of females and males, and program content was gender neutral. Conclusions Findings highlight a range of available services, and a number of varied service-user experiences and perspectives, in these rural areas. Key service gaps were identified, and caregivers made some specific recommendations to address these gaps. Findings underscore multiple opportunities to inform service delivery and program participation for rural and remote people living with dementia and their families.